Leadership Member Exchange Relationships on the Work Engagement of Physical Education Teachers - Gao, Jia (International Journal of Social Sciences and Public Administration, 2024)
This study tries to take the group of physical education teachers in Zhaoqing City as the research object, focuses on the two variables of physical education teachers' leadership member exchange and work input, and researches the current situation of their variables,  to find the correlation between the leadership member exchange of physical education teachers in Zhaoqing City and physical education teachers' work input with the help of the theory of leadership exchange and explores the optimization countermeasures of the leadership member exchange on the work input of physical education teachers as a guide to enhance the motivation of physical education teachers to work, provides a price basis for the promotion of the relationship between physical education teachers and leaders.